Creation of Digital Educational Technologies by School Subjects - Marina Bazzo de Espíndola; Rosely Zen Cerny; Julia Maria Gerhardt da Rocha; Francisco Fernandes Soares Neto (Universidade de Lisboa, 2022)
This article analyses whether, and how, the creation of digital technologies by basic education teachers subsidizes the process of critical appropriation of digital technologies towards their professional emancipation. The research is based on materials produced during meetings with teachers from three schools. The content analysis resulted in the emergence of the following categories: 1 - lack of autonomy in relation to educational technologies; 2 - development of a critical perspective of technologies; and 3 - paths for critical integration of technology in the school - which resulted in two subcategories: 3.1 - Critical adaptation of technologies; and 3.2 - Creation of new technologies in alignment with school needs. It becomes clear that the school is a privileged space for the production of educational technologies based on the real needs of its actors, to contribute to overcoming historical challenges and the effective transformation of contemporary education.